Thermostability and thermodynamic characterization of sprouted pearl millet ?-amylases for its biotechnological applications - Agbo, KU; Okwuenu, PC; Ezugwu, AL; Eze, SOO; Chilaka, FC (Bangladesh Journal of Scientific and Industrial Research, 2017)
There is an increasing demand for amylolytic products such as glucose syrup in biotechnological industries. Starch liquification by ?-amylase must take place at temperatures higher than the gelatinization temperatures and the use for thermostable ?-amylase is therefore required. Two (or) isotypes namely amy-1 and amy-2 of ?-amylase from pearl millet have been investigated for their thermostability and thermodynamic characterization. Thermal inactivation of ?-amylase follows first order kinetics which varies with time and product during inactivation process. The half-life of ?-1 was 198 mins at 50°C. The Ea (inact) was calculated using Arrhenius plot gave 22.00 KCalmol-1K-1 for ?-1 and 19.44 KCalmol-1K-1 for ?-2. The Z-values were 22.52°C and 25.38°C for ?-1 and ?-2, respectively. The thermodynamic parameters: the enthalpy change of inactivation ?H (inact) had 87.815 KJmol-1K-1 at 50°C for ?-1 and 78.56 KJmol-1K-1 at 50°C for ?-2. The change in free energy of inactivation ?G (inact) of ?-1 and ?-2 were 105.5 KJmol-1K-1 and 104.33 KJmol-1K-1 at 50°C, respectively. The entropy of inactivation ?S (inact) values for ?-1 and ?-2 are calculated as -54.80 JMol-1K-1 and -79 JMol-1K-1 at 50°C. This suggest that the ?-1 and ?-2 are thermostable. Bangladesh J. Sci. Ind. Res. 52(3), 159-166, 2017